The Importance of Preventive Maintenance on Cnc Laser Cutting Machines: Maintaining Quality Consistency and Avoiding Unexpected Damage - Hermawan, Reza; Supriyatna, Deddy; Susilo, Eko (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The development of the manufacturing industry is driven by society's demand for goods and services, with CNC laser cutting machines playing a crucial role due to their speed, accuracy, and flexibility. This article emphasizes the importance of preventive maintenance to maintain optimal performance, avoid downtime, and extend the machine's lifespan. Through literature studies and surveys, the research highlights the significance of routine checks on key components, cleaning, the use of checklists, and the detection of potential damage. Challenges include the need for skilled technicians, proper equipment, and team coordination. Systematic preventive maintenance enhances operational efficiency, reduces costs, and ensures uninterrupted machine performance, with careful planning and continuous training being key to success.